Perspektif Orang Tua Pada Kekerasan Verbal Anak Usia Dini - Sukma Olii; Jamin, Nunung Suryana; Waode Eti Hardiyanti (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2023)
The data collection method consisted of interviews and documentation. Based on the study rationale, it was concluded that parental perspectives on verbal violence in early childhood have a negative impact. Despite being less visible, verbal violence has significant consequences for its victims. Several factors supported the data, including the respondent’s knowledge and educational background. The data from the respondents' answers further support the above statement, as 15 individuals agreed that threatening a child is one form of verbal violence. Additionally, the development aspects and parenting styles used on children can also influence the occurrence of verbal violence toward them. Hence, efforts are required to address verbal violence, including 1) Parents should learn about different parenting styles. 2) Parents should understand verbal violence and its negative impacts, which can affect a child's development.